Randomization methods and cluster size in cluster randomized trials conducted in elementary and high schools - Pajčin, Mirjana; Bukumirić, Zoran; Tomašević, Jelena; Ilić, Aleksandra (Vojnosanitetski pregled, 2022)
Background/Aim. Randomization allows for study groups to be formed so that they are similar in all characteristics except outcomes. The aim of this study was to examine the frequency of randomization methods and their effect on achieving baseline balance in cluster randomized studies conducted in schools. Methods. A literature search of the Medline bibliographic database showed that the total number of collected articles in the full text was 343, out of which 81 were eligible for inclusion. Each publication was reviewed by two independent reviewers, and data were extracted and analyzed. Results. Stratification was the most commonly applied randomization method, reported in 28 trials (34.6%). There was no statistically significant difference in the number of subjects and clusters, as well as in cluster size between trial groups in studies in which simple randomization was applied. However, there was a statistically significant difference in the number of subjects and clusters between groups in trials in which restricted randomization methods were used. Yet, there was no difference in the cluster size. Conclusion. Although there is no difference in the size of clusters between trial arms, either at the level of the entire sample or in relation to randomization methods applied, additional research should be conducted on a larger sample in order to establish the effect of randomization methods on baseline balance, when the size of clusters is in question.